EVALUATION OF OPTIMAL PARAMETERS IN THE DEVELOPMENT OF DETECTED SEWING AND SEWING DEFECTS - Ismailov Nurulla Tuichibayevich; Mamatkulova Saida Rakhmatovna; Abdulbaki Rakhmonov; Bobozhanov Husankhan Takhirovich (Web of Journals Publishing, 2024)
In the proposed sewing and knitting production, when sewing and stitching products made of knitted fabrics to ensure high-quality and durable seams of materials with high elastic properties, the rotation speed of the main shaft of the sewing machine, (min. -1), the pitch of the sewing machine, (mm), the hardness of the seam, defects found in the seam and the role of the jumping needle are of great importance the value as a result of evaluating and applying the optimal one. The parameters of such sewing machines, the possibility of producing cheap and competitive knitted fabrics that can replace imports in our republic simultaneously in the sewing and knitting industries, will be a new step in sewing technologies.
Keywords: Regression equation, physical and mathematical model, Fisher criterion, needles, sewing machine, finished fabric.